2018
DOI: 10.3920/wmj2017.2294
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of producers of small lactone mycotoxins: patulin, penicillic acid and moniliformin

Abstract: A very large number of filamentous fungi has been reported to produce the small lactone mycotoxins patulin, penicillic acid and moniliformin. Among the 167 reported fungal producers of patulin, only production by 29 species could be confirmed. Patulin is produced by 3 Aspergillus species, 3 Paecilomyces species, 22 Penicillium species from 7 sections of Penicillium, and one Xylaria species. Among 101 reported producers of penicillic acid, 48 species could produce this mycotoxin. Penicillic acid is produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 289 publications
(291 reference statements)
0
62
0
2
Order By: Relevance
“…Meanwhile, the HPLC analysis of this extract revealed that it contained dihydropenicillic acid as its major constituent, as seen in Figure 1 and 2. Several fungi have been reported to produce dihydropenicillinic acid, and its unsaturated analogue, penicillic acid, and these include Aspergillus flavus, Aspergillus ochraceus, Aspergillus terreus, Penicillium cyclopium and Penicillium griseofulvum 44 . A previoius study revealed that dihydropenicillinic acid displayed moderate cytotoxicity against several human cancers including human non-small cell lung cancer, human breast cancer, human CNS cancer and human pancreatic cancer at 10 µg/mL 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the HPLC analysis of this extract revealed that it contained dihydropenicillic acid as its major constituent, as seen in Figure 1 and 2. Several fungi have been reported to produce dihydropenicillinic acid, and its unsaturated analogue, penicillic acid, and these include Aspergillus flavus, Aspergillus ochraceus, Aspergillus terreus, Penicillium cyclopium and Penicillium griseofulvum 44 . A previoius study revealed that dihydropenicillinic acid displayed moderate cytotoxicity against several human cancers including human non-small cell lung cancer, human breast cancer, human CNS cancer and human pancreatic cancer at 10 µg/mL 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Patulin (PAT) is produced by many different molds, predominantly by Penicillium spp. (Puel et al, 2010;Frisvad, 2018;Vidal et al, 2019) but, occasionally, by some Byssochlamys (Sant'Ana et al, 2010;Frisvad, 2018) and Aspergillus spp., including A. giganteus, A. longivesica, and A. clavatus (Varga et al, 2007;Pal et al, 2017;Frisvad, 2018) as well. Chemically, PAT is a water-soluble, colorless, polyketide lactone (Figure 3), which is thought to exert its toxicity through reacting with thiol groups (cysteine, glutathione, thiol moieties of proteins) in the cytoplasm (Pal et al, 2017).…”
Section: Patulinmentioning
confidence: 99%
“…Furthermore, A. clavatus may also colonize malted barley and wheat, which might also contribute to the appearance of PAT in the feed and food chain (Lopez-Diaz and Flannigan, 1997;Loretti et al, 2003;Sabater-Vilar et al, 2004). Different food products, like vegetables, rotting apples, grains, and fruits may contain primarily Penicillium-derived PAT (Puel et al, 2010;Wright, 2015;Frisvad, 2018;Vidal et al, 2019). As this is a quite stable secondary metabolite, it can withstand various harsh processing steps, such as milling and heating.…”
Section: Occurrence Of Aspergillus-derived Mycotoxins In the Feed Andmentioning
confidence: 99%
“…Patulin production is often detected within the decayed area, which is majorly caused, by P. expansum and other pathogenic Penicillium . In a recent study, among the 166 fungal isolates that have been reported to produce patulin, 77 belong to pathogenic Penicillium [ 37 ]. As a psychrophilic fungus, P. expansum grows well at 0 °C or even −2/−3 °C, so infection can still take place during the cold storage of apples [ 43 ].…”
Section: The Burdens Of Patulin Accumulation In Apples and Apple Pmentioning
confidence: 99%
“…Moreover, the conventional control of blue mold decay by fungicides also concerns the public by itself, because of the potential risks of such chemicals to human health. In the view of blue mold and patulin, studies from the past decade have reviewed patulin-producing strains and their biosynthesis genes [ 36 , 37 ]. Considering that patulin is often detected in apples products, factors that affect patulin production in apple fruits, conventional practices for postharvest control, and the fate of patulin during juice processing have been discussed [ 32 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%